2014
DOI: 10.3109/09638237.2014.924047
|View full text |Cite
|
Sign up to set email alerts
|

Depression is linked to uncontrolled hypertension: a case–control study from Karachi, Pakistan

Abstract: There is association between uncontrolled hypertension and depression that is independent of sociodemographic factors, comorbids and history of hospitalization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
28
1
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(40 citation statements)
references
References 37 publications
(35 reference statements)
7
28
1
4
Order By: Relevance
“…A recent case-control study from Pakistan showed a significant association between uncontrolled HT and depression evaluated by HADS. 47 Symonides et al 48 have recently proposed that the suppression of negative emotions adversely affect BP control evaluated by ABPM in treated hypertensive patients. All of these reports support our results.…”
Section: Discussionmentioning
confidence: 99%
“…A recent case-control study from Pakistan showed a significant association between uncontrolled HT and depression evaluated by HADS. 47 Symonides et al 48 have recently proposed that the suppression of negative emotions adversely affect BP control evaluated by ABPM in treated hypertensive patients. All of these reports support our results.…”
Section: Discussionmentioning
confidence: 99%
“…Os sintomas da depressão podem afetar a QV (24) , a adesão ao tratamento medicamentoso e não medicamentoso de pessoas com hipertensão, além de predispor a hábitos inadequados, devido principalmente as alterações de humor que ela ocasiona (11) , podendo predispor ao aparecimento de complicações.…”
Section: Discussionunclassified
“…Nele, foram incluídos 590 pacientes que se apresentaram em dois ambulatórios com pressão arterial acima de 140/90 mmHg. Os resultados demonstraram que houve associação entre hipertensos não controlados e história de depressão (24) . Em estudo realizado no Rio Grande do Sul, Brasil, com 302 pacientes para verificar a associação entre sintomas de ansiedade ou depressão, HA e seu impacto na QV, utilizando-se os questionários de Beck e o SF-36, demonstrou que a depressão e a ansiedade influenciam negativamente na QV (25) .…”
Section: Discussionunclassified
“…Being directly linked, and having numerous interactions with other health conditions (Almas et al, 2014), mental health cannot be separated from other health domains, and is essential for sustainable human development (Prince et al, 2007). In the Constitution of the World Health Organization, mental health is an integral part of health and well-being (World Health Organisation, 2006).…”
Section: Mental Health Presents Cross-cutting Issues For Health and Dmentioning
confidence: 99%